Malignancy and IgG4-related disease: the incidence, related factors and prognosis from a prospective cohort study in China - Tang, Hanqi; Yang, Huaxia; Zhang, Panpan; Wu, Di; Zhang, Shangzhu; Zhao, Jiuliang; Peng, Linyi; Chen, Hua; Fei, Yunyun; Zhang, Xuan; Zhao, Yan; Zeng, Xiaofeng; et al. (Scientific reports, 2020)
This prospective cohort study aims to investigate the incidence, related factors and prognosis of IgG4-related disease (IgG4-RD) with malignancies in the Chinese cohort. We prospectively analyzed the IgG4-RD patients recruited in Peking Union Medical College Hospital from January 2011 to August 2018 and identified patients diagnosed with IgG4-RD complicating malignancies. Data regarding demographics, clinical features, treatment and prognosis of IgG4-RD patients complicating malignancies were collected and compared to those of age- and sex-matched controls. Among the 587 Chinese patients with IgG4-RD, 17 malignancies were identified. Ten of them developed malignancy after the diagnosis of IgG4-RD, given a standard incidence ratio (SIR) of 2.78 (95%CI 1.33–5.12). Multivariate logistic analysis indicated that autoimmune pancreatitis (OR = 6.230, 95%CI 1.559–24.907, p = 0.010) was positively associated with malignancy, whereas eosinophilia (OR = 0.094, 95%CI 0.010–0.883, p = 0.039) was negatively related with malignancies. During a median follow-up period of 61.4 ± 26.4 months, all patients with IgG4-RD and malignancies survived. We conclude that an increased incidence of malignancy was found in Chinese IgG4-RD cohort. Autoimmune pancreatitis is a potential risk factor, whereas eosinophilia is a possible protective factor for complicating malignancies.